Reason and eros - Chalmers, W D (Rhodes University, Faculty of Humanities, Department of Philosophy, 1967)
This study is not intended as a work of research into any existing body of philosopny. It is, rather, an independent inquiry into the origins and the objective of philosophical activity. In this it assumes the somewhat enigmatic role of a philosophy of philosophy.
Keywords: Philosophy; Love; Reasoning